A response: Blue washing, ontology, eschatology and exploitation. (28th January 2019) - Scott, Matt
Abstract: The article is reflexive and critically engaged response to the articles in the Special Issue and a consideration of the meaning(s) and application that are suggestive of a new materialism and ontology of water. The main strands and key points of each article are clustered, compared and contrasted and an analysis is applied in order to review their practical applications. The intellectual logic and coherence is tested and notes that the trope of water is both highly suggestive and transgressive. The new ontology and materialism that is both implied and developed by the articles is deeply subversive and this undercutting and moving away from more traditional rigid frameworks and conceptualization is considered and recognized as an important and exciting assertion of a new holism and articulation of environmental values transcending human agency. A personal praxis introduces and concludes the response which makes the connection with the author's own community development work.